Educational Policy in Post-Crisis Yemen: Between Regulatory Ideals and Implementation Constraints (International Journal of Education and Literature, 2025)
Yemen's protracted crisis has severely disrupted the educational sector, rendering the implementation of national education policies inconsistent and largely ineffective. This article explores the major challenges faced in executing educational policies in post-crisis Yemen, focusing on the gap between well-formulated regulatory frameworks and the realities of field implementation. Drawing upon a qualitative literature review and document analysis, the study identifies several critical barriers, including political instability, inadequate infrastructure, funding shortages, and regional disparities. The analysis also highlights the resilience of local actors and communities who often act as de facto education providers in the absence of centralized governance. Findings suggest that the success of post-crisis education policy in Yemen depends not only on formal regulation but also on adaptive, community-driven implementation mechanisms. The study concludes with strategic recommendations to bridge the policy-practice gap through decentralized governance, international partnerships, and targeted investment in teacher development and school reconstruction. These insights contribute to a broader understanding of educational recovery in fragile and conflict-affected settings.